Pengaruh Profitabiltias, Likuiditas, Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi - Aulia Zulfa; Liza Novietta; Mhd Karya Satya Azhar (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
This study aims to determine the effect of Profitability, Liquidity, Company Size on Firm Value with Capital Structure as a moderating variable. This type of research is a type of quantitative research. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used was purposive sampling method with a sample of 71 companies w. The data analysis technique of this research used Moderated Regression Analysis (MRA) using residual test. The results of this study indicate that profitability, liquidity and company size have an effect on firm value. Capital Structure is able to moderate the effect of Liquidity on Company Value, but Capital Structure cannot moderate the effect of Profitability and Company Size on Firm Value in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2016-2020 period.